Word of Mouth Marketing: Perempuan sebagai Sales Forces dan Persuader dalam Dinamika Kelompok Bisnis Tupperware - Kartika, Widyaningtyas Virgo; Suparno, Basuki Agus; Rochayanti, Christina (Jurnal Ilmu Komunikasi, 2025)
Marketing communication plays a crucial role in the overall mission of marketing, serving as a key determinant of its success. One of the most influential forms of this communication is word-of-mouth marketing (WOMM), which has become a powerful force in direct marketing. Interestingly, WOMM is often driven by women, who, based on various studies, possess significantly stronger verbal communication abilities than men. This makes the phenomenon of women engaging in WOMM—particularly as part of the sales force for Tupperware within women communities in Kulon Progo Regency—both compelling and important to explore. These women operate in a dual role: as persuasive marketers and as loyal consumers. This study employs a case study approach, focusing on a community of Tupperware users in Kulon Progo. The findings reveal that WOMM, as carried out by women in both their roles as sellers and consumers, contributes meaningfully to building brand equity and fostering repurchase intentions within the community. Women emerge not only as unique consumers with a strong sense of group cohesion but also as persuasive influencers who drive others toward purchase decisions. In this context, they are both the persuaders and the driving force behind increased sales and sustained product loyalty for Tupperware.